Effects of process conditions on the chemistry of an Ar/C 2H 2 dust‐forming plasma. Issue 6 (2nd April 2019) - Denysenko, Igor B.; von Wahl, Erik; Labidi, Safa; Mikikian, Maxime; Kersten, Holger; Gibert, Titaϊna
Abstract: A volume‐averaged model and numerical simulations are used to clarify the effects of process conditions on the plasma chemistry and species initiating the formation of nanoparticles in an Ar/C2 H2 plasma. It is shown that Ar/C2 H2 plasmas with low electron density, moderate input flux of acetylene and an electron energy distribution function (EEDF) close to the Druyvesteyn EEDF are the most suitable for the production of carbonaceous nanoparticles. These results are verified by direct comparison with experimental data and enable to formulate recommendations for future experiments with a controlled growth of nanoparticles in chemically active plasmas. Abstract : Properties of an Ar/C2 H2 plasma are studied using a volume‐averaged model for the process conditions of our experiments on nanoparticle growth. It is analyzed how the densities of plasma species, initiating the formation of carbonaceous nanoparticles, depending on the input power, the acetylene input flux, the shape of the electron energy distribution function and the density of nanoparticles.